Legal Protection of Street Children Post-Natural Disaster in Palu Based On The Family Empowerment Model - Kartini Malarangan (Fakultas Hukum Universitas Lampung, 2021)
Street children have a negative impact on the stigma of child growth. Street children depend their lives on the streets because of economic, social or even family conditions that do not support their development. After the natural disaster, 28 September 2018 was the point where areas were affected, especially in the areas of Palu, Sigi and Donggala (Pasigala). The phenomenon that occurs when a disaster occurs, robs them of their finances, such as their homes and their livelihoods. The increasing number of street children will certainly affect the number of crimes committed considering the harshness of street life and the bad friendship environment can make a child who has never been faced with the law becomes a child who is dealing with the law. So in this case it is necessary to protect the law for street children. So that the main problem in this research is what are the factors that dominate a child being a street child in the Post-Natural Disaster Post Wolf Area, and how is the Model for Handling Street Children Post-Natural Disasters through an Innovation System Based on Family Empowerment. The results of this study indicate that legal protection for street children after natural disasters qualifies with the adoption of the family empowerment model by presenting the Tina Nu Ngata model.